Terceira onda de autocratização na América Latina : retrocessos e colapsos democráticos no Brasil e na Venezuela em perspectiva comparada - Diego Prata Melo (2024)
There has been a consensus among political scientists that the “death of democracy” would not be a phenomenon resulting only from sudden events, such as military coups and the closure of Congress. In this new situation, called the “third wave of autocratization (1994-2023), the reversal of democracy occurs gradually and through legal channels (LÜHRMANN & LINDBERG, 2019). In Latin America, this process occurs with its own intensities and dynamics,since economic crises, constant socioeconomic problems, the strength and frequent interference of “praetorian” actors in the political arena and the fragile commitment of elites to (formal and informal) democratic institutions would continue to be an obstacle to the institutionalization of popular sovereignty. These typical causal conditions of the region came to be collectively called latinamericanización (LEVINE, 1994). ITherefore, the “third wave” that is manifesting itself in Latin America has its own aggravating factors that could potentially put democracy at risk. That said, the question that guided the research was: how do political, socioeconomic and cultural factors contribute to inserting Latin America into the third wave of autocratization? In order to answer this question, the research object was defined as the events that weakened the democracies of Brazil and Venezuela, according to the democratization scores recorded by the Varieties of Democracy Project (V-Dem). The hypothesis was that the combination of poor socioeconomic performance, weak citizen support for democracy and radical and disloyal coalitions would form a sufficient condition to explain the phenomenon of interest. Through the Qualitative-Comparative Approach (QCA), it was concluded that anti-democratic political coalitions constitute a sufficient condition to explain the democratic setback.